Perineal Massage for Prevention of Perineal Trauma and Episiotomy During Labor: A Systematic Review and Meta-analysis - Vijayakumar Venugopal; Boopalan Deenadayalan; Kuppusamy Maheshkumar; Cithamparam Yogapriya; Anandhan Akila; Muthupandi Pandiaraja; Shanmugam Poonguzhali; Ravi Poornima (Tehran University of Medical Sciences, 2022)
Objective: Vaginal births are associated with a certain degree of trauma to the genital tract, with significant short-term and long-term morbidity. Awareness of morbidity following perineal trauma has led to application of different interventions during the late first stage and second stage of labour to prevent severe perineal trauma. This includes techniques such as perineal massage, warm and cold compresses, and perineal management techniques. Objective of this meta-analysis is to evaluate the effect of perineal massage during the late first stage and second stage of labour on the rate of episiotomy and risk of perineal trauma. Materials and methods: Electronic databases (PubMed, Scopus, Cochrane Library and Science Direct) were searched from inception until August 2021. We included randomized controlled trials (RCTs) which compares perineal massage during labor (i.e., intervention group) with a control group in women with singleton gestation and cephalic presentation at ≥36 weeks. The primary outcome was severe perineal trauma and the rate of episiotomy. Meta-analysis was performed using the random-effects model of DerSimonian and Laird to produce summary treatment effects in terms of relative risk (RR) with 95% confidence interval (CI). Results: Ten trials including 4,088 women were analyzed. Women with perineal massage during labor had a significantly lower incidence of severe perineal trauma (RR: 0.52, 95% CI 0.29- 0.94) compared to the control group. The incidence of episiotomy was lower in the perineal massage group (RR: 0.71, 95% CI 0.52-0.98 p < 0.01) but was statistically insignificant (P>0.05). Conclusion: The finding of meta-analysis showed that perineal massage during labor could be effective in reducing the risk of severe perineal trauma, such as third- and fourth-degree spontaneous lacerations during labor.